Civil War in Syria: External actors and interests as drivers of conflict - Muriel Asseburg; Heiko Wimmen (Stiftung Wissenschaft und Politik (SWP), 2012)
The armed conflict in Syria has accelerated in recent months. Both regime and rebels see themselves in a fight for survival that leaves no room for compromise. External supporters of both sides treat the conflict as a zero-sum game with far-reaching and, for some actors existential, consequences for their own strategic positions, and are therefore determined to prevent any outcome they would regard as disadvantageous. Their diplomatic, financial and in some cases military support fans the flames of conflict and strengthens the hand of hardliners on both sides. For the foreseeable future, there is good reason to expect that the conflict will be neither resolved politically nor won militarily. The priority for Europeans should be to stem the violence and support inclusive civilian structures; the latter could contribute to improving living conditions at the local level and counteracting radical and centrifugal tendencies
Keywords: 320